Analysis of the geographic distribution of the Prosopis complex (Leguminosae, Mimosoideae) in North America - Rzedowski, Jerzy (Instituto de Ecología, A.C., 1988)
The geographic distribution of the North American species of the Prosopis-complex is illustrated and discussed. Out of the total of 10, 3 species belong in the section Strombocarpa, 6 in the section Algarobia and one in the genus Prosopidastrum, 3 taxa considered in Burkart's (1976) taxonomic treatment as parallel evolutionary lines. lt is concluded that the joint picture given by the distribution areas suggests a considerable antiquity in terms of permanence of the group in arid North America. On the other hand, the presence of P. juliflora in Central America and in northern South America is interpreted as an indication of a transequatorial migration route and not as the point of departure of a convergent evolution in dry areas on both sides of the tropical belt.